Metal-free synthesis of 3-trifluoromethyl-1,2,4-triazoles via multi-component reaction of trifluoroacetimidoyl chlorides, hydrazine hydrate and benzene-1,3,5-triyl triformate - Wang, Binjie; Sun, Yue; Cheng, An; Zhu, Yeanlun; Wang, Jiye; Chen, Zhengkai; Wu, Xiao-Feng (Frontiers in Chemistry, 2022)
A convenient approach for the construction of pharmaceutically valuable 3-trifluoromethyl-1,2,4-triazoles has been developed, which employs the readily available trifluoroacetimidoyl chlorides, hydrazine hydrate and benzene-1,3,5-triyl triformate (TFBen) as starting materials. The multi-component reaction features broad substrate scope, high efficiency, and scalability, providing a facile and straightforward route to the biologically important 3-trifluoromethyl-1,2,4-triazole scaffolds in moderate to good yields. Considering its broad-spectrum pharmaceutical activity, the method offers the opportunity for the further study towards the toxicity risk assessment and structure-activity relationship of the pharmaceuticals containing trifluoromethyl-1,2,4-triazole cores.